Form or Flesh: Social Factors that Impact Women’s Practice of Breast Self-Examination - Patricia A. London (Adult Education Research Conference, 2002)
The purpose of the qualitative study was to understand the meanings of the social factors identified by Caucasian middle-class women and their practice of breast self-exam (BSE). The meaning of breast selfexam is discussed in relationship to body image and the social definition of being a woman.